Comparing the Efficiency and Scalability in JAMstack and LAMP-based Monolithic WordPress : An in-depth examination of the development processes, performance benchmarks, and scalability characteristics found in modern web architectures - Huusko, Aleksi (My University, 2024)
The evolution of web development architectures has introduced various paradigms, each promising improvements in performance, scalability, and ease of use. Among these, JAMstack (JavaScript, APIs, and Markup) has gained attention for its decoupled nature and modern approach, while traditional monolithic architectures, particularly those employing the LAMP (Linux, Apache, MySQL, PHP) stack, remain prevalent due to their robustness and extensive ecosystem. This thesis presents a comprehensive comparative analysis of the efficiency and scalability of JAMstack and LAMP-based Monolithic WordPress architectures. The primary objective of this research is to evaluate the two architectures in terms of development efficiency, performance, and scalability under varying traffic conditions. To achieve this, two prototypes were developed: a JAMstack application using React, Next.js, and a headless WordPress backend with WPGraphQL, and a traditional monolithic WordPress site running on a LAMP stack. The findings provide valuable insights for developers and businesses in selecting the most suitable architecture for their web projects, balancing factors such as performance, scalability, development complexity, and maintenance. This thesis contributes to the field of web development by highlighting the trade-offs between modern and traditional architectural paradigms, offering a detailed analysis that guides informed decision-making in the context of contemporary web development needs.
Keywords: JAMstack, LAMP, Monolithic WordPress, Web Development Architectures